RELIGIOSITY, FINANCIAL KNOWLEDGE, AND FINANCIAL BEHAVIOR INFLUENCE ON PERSONAL FINANCIAL DISTRESS AMONG MILLENNIAL GENERATION - Nelson Lajuni; Imbarine Bujang; Abd. Aziz Karia; Yusman Yacob (Jurnal Manajemen dan Kewirausahaan, 2018)
This study attempts to examine the personal financial distress among Malaysians millennial generation by scrutinizing religiosity, financial knowledge, and financial behavior as the influencing antecedents. The study adopted social learning theory (SLT) to underpin and explain the conceptual framework. The data were collected from millennial generations in Malaysia and analysed using Partial Least Squares Structural Equation Modelling. The findings suggest that all claimed hypotheses were partially supported. Implication and contribution of the study were later discussed to justify the significance of this research. The findings revealed that behavioral traits to have a stronger impact on the incidence of personal financial distress than religiosity or financial knowledge. The results suggested the government should implement policy that could be oriented towards improving the financial habits and mitigating the impact of behavioral characteristics on personal finances